2012
DOI: 10.1111/j.1365-2591.2012.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire study to derive information on the working environment, clinical training, use of ancillary staff and optimization of patient radiation dose within UK dental practice

Abstract: Both Endodontists and GDPs demonstrated compliance with guidelines relating to radiation protection being more significant amongst those clinicians working within specialist clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Previous studies have reported differences between specialists and general dentists with regard to the use of rectangular collimation38 and selection criteria 17. The results of the current study suggested that specialists were more knowledgeable about selection criteria and radiation safety; however, even specialists showed little interest in explaining radiation risks and benefits to patients, utilizing bitewing technique, or applying rectangular collimation.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have reported differences between specialists and general dentists with regard to the use of rectangular collimation38 and selection criteria 17. The results of the current study suggested that specialists were more knowledgeable about selection criteria and radiation safety; however, even specialists showed little interest in explaining radiation risks and benefits to patients, utilizing bitewing technique, or applying rectangular collimation.…”
Section: Discussionmentioning
confidence: 49%
“…In general, the results reflected poor awareness toward x-ray exposure and precautions, similar results revealed from others, [1,3,10] but from the literature; one study concluded that radiation protection measures were more significant amongst clinical specialists. [20] In addition, a significant correlation between gender and awareness of usefulness of collimators and filters in dental radiography was noted, with females being more aware than males. The same association was reported in the Belgian study [18] and this may explained that female dentists might have experienced the use of lead aprons during pregnancy.…”
Section: Discussionmentioning
confidence: 98%